2015
DOI: 10.1002/poc.3513
|View full text |Cite
|
Sign up to set email alerts
|

The ESIPT mechanism of dibenzimidazolo diimine sensor: a detailed TDDFT study

Abstract: Spectroscopic investigations on excited state proton transfer of a new dibenzimidazolo diimine sensor (DDS) were reported by Goswami et al. recently. In our present work, based on the time-dependent density functional theory (TDDFT), the excited-state intramolecular proton transfer (ESIPT) mechanism of DDS is studied theoretically. Our calculated results reproduced absorption and fluorescence emission spectra of the previous experiment, which verifies that the TDDFT method we adopted is reasonable and effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 50 publications
(47 reference statements)
1
14
0
Order By: Relevance
“…And the large Stokes shift could be attributed to the four energy level photophysical and photochemical behavior with the creation of photochromic tautomer in the ground state. [21][22][23][24][25][26][27][28][29][30] Independently of the application, the understanding of the dynamics between proton donor and acceptor sites in the electronic excited states is an important task. The model formulated by Weller is composed of a fourlevel photochemical cycle where the phototautomerization process happens.…”
Section: Introductionmentioning
confidence: 99%
“…And the large Stokes shift could be attributed to the four energy level photophysical and photochemical behavior with the creation of photochromic tautomer in the ground state. [21][22][23][24][25][26][27][28][29][30] Independently of the application, the understanding of the dynamics between proton donor and acceptor sites in the electronic excited states is an important task. The model formulated by Weller is composed of a fourlevel photochemical cycle where the phototautomerization process happens.…”
Section: Introductionmentioning
confidence: 99%
“…And this kind of process has been widely investigated in the past few years due to their significant characteristics in biological and chemical fields. In effect, these changes about properties have been extensively applied to fluorescent sensing technologies, fluorescence imaging, organic light‐emitting diodes (OLEDs), and so forth . However, some mechanisms of the ESPT reactions are complicated.…”
Section: Introductionmentioning
confidence: 99%
“…In effect, these changes about properties have been extensively applied to fluorescent sensing technologies, fluorescence imaging, organic lightemitting diodes (OLEDs), and so forth. [31][32][33][34][35][36][37][38][39][40] However, some mechanisms of the ESPT reactions are complicated. The mechanisms of PT, such as the sequence of PT in the dual-PT system as well as the mode of PT, and so forth, could not be obtained by spectra technologies.…”
Section: Introductionmentioning
confidence: 99%
“…ESIPT process has been a popular research field since 1956, firstly reported by Weller and coworkers in experiment with methylsalicylate . In fact, the transferred tautomerization form (normally named keto in the S 0 state and keto* in the S 1 state) has charge redistribution characteristic, which are very fascinating towards the application of laser dyes, UV filters, fluorescence chemosensors, molecular switch, and so on . At experimental level, the excited state proton transfer processes can indeed be followed using ultrafast pump‐probe and time‐resolved emission experiments or coherent Raman methods.…”
Section: Introductionmentioning
confidence: 99%
“…[29,30] In fact, the transferred tautomerization form (normally named keto in the S 0 state and keto* in the S 1 state) has charge redistribution characteristic, which are very fascinating towards the application of laser dyes, UV filters, fluorescence chemosensors, molecular switch, and so on. [31][32][33][34][35][36][37][38][39][40] At experimental level, the excited state proton transfer processes can indeed be followed using ultrafast pumpprobe and time-resolved emission experiments or coherent Raman methods. Furthermore, some molecules are highly sensitive to the change in the microenvironments, based on which Sytnik et al reported how the ESIPT chromophores can be used in the study of protein conformations and binding site polarity.…”
Section: Introductionmentioning
confidence: 99%